Analisis Pengaruh Integritas Terhadap Kinerja Pegawai pada Badan Pengelola Keuangan, pendapatan dan Aset Daerah Kabupaten Tapanuli Tengah - Nanda Pratama Panggabean; Anna Basriani; Sinta Veronika Hutabarat; Indra Setiawan Hutabarat; Hendra Sahputra (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of integrity on employee performance at the Regional Financial, Revenue, and Asset Management Agency (BPKPAD) of Central Tapanuli Regency. The research method used is a quantitative approach with a correlational design. Data were collected through questionnaires distributed to employees. The results showed a strong and positive relationship between integrity and employee performance. The correlation coefficient value (r) was 0.62, indicating a significant relationship between the two variables. Furthermore, the determination coefficient analysis revealed that integrity contributes 39% to employee performance, while the remaining 61% is influenced by other factors not examined in this study. These findings suggest that increasing employee integrity can positively affect performance outcomes at BPKPAD Central Tapanuli Regency.